(untitled) (Research, Society and Development, 2021)
The promotion of active learning that combines theory and practice in order to result in the autonomous construction of knowledge is one of the challenges present in the current context of higher education. The objective of this work is to analyze the use of real situations as a promoter of meaningful learning in the scope of information systems. Based on experience in an undergraduate course in the computer science course, the teaching strategy and teaching resources adopted are analyzed. The teaching strategy object of study was the analysis of problem situations, while the didactic resources analyzed were a problem-solving model in information systems and a business process modeling technique. The teaching strategy and didactic resources in question were used to analyze the applicability of a real problem situation. It was found that the said teaching strategy can promote meaningful learning. It was also verified that the use of the didactic resources in question, makes it possible to identify not only technological issues of information systems solutions, but also contemplating human and organizational issues. The study points to the potential for replicability of strategy and didactic resources for teaching and active learning in information systems and makes it possible to conclude on the importance of prior planning of teaching strategies and the appropriate choice of teaching resources.